The Diffusion of Labour Standards: The Case of the US and Guatemala - van Roozendaal, Gerda (2015)
The number of free trade agreements (FTAs) concluded by the United States of America (US) has grown vastly over the past two decades. While FTAs contribute to increased global competition and as such may also contribute to socially-undesirable practices in the area of working conditions and the environment, the proliferation in FTAs has paradoxically also augmented the potential for making free trade more fair as some of these agreements now include labour provisions. However, the question is whether these trade agreements have also actually diffused internationally recognised labour standards. This article studies the FTA the US signed in 2004 with a number of Central American countries and which, at a later stage, also included the Dominican Republic. This FTA is commonly referred to as CAFTA-DR and includes a chapter on labour standards. The article argues that the effects of the inclusion of labour standards in CAFTA-DR have been limited and therefore should be viewed as an unsuccessful attempt at policy transfer. This is illustrated by the case of Guatemala, a country known for its lack of respect for labour standards and which is currently the subject of a complaints procedure under the CAFTA-DR. It is maintained that this lack of effectiveness is the result of many factors. Among these is the weakness of the labour chapter of CAFTA-DR resulting from the fact that the chapter is the outcome of bargaining processes both within the US and between the US and Guatemala, where symbolic results were valued more highly than actual substance.